2011
DOI: 10.1016/j.hlc.2011.05.397
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Annulus Diameter Determination by Multidetector Computed Tomography: Reproducibility, Applicability and Implications for Transcatheter Aortic Valve Replacement

Abstract: S Heart, Lung and CirculationAbstracts S159 2011;20S:S156-S251 incentive survey with 65 multichoice questions covering all aspects of the service (indications, contraindications, image settings, safety, echo lab workforce and workflow issues and clinical relevance). These answers and a free text option were analysed to assess the program and to determine whether this survey method may be an adequate quality control measure. This survey was approved by the hospital's Human Research Ethics Committee.Results: Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
77
0
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 0 publications
5
77
0
5
Order By: Relevance
“…Numerous studies have shown the advantages of 3D assessment of the annulus compared with 2D assessment using multiple modalities, including MDCT, 3,5,6,16,20,35,36 3D-TEE, [7][8][9]11,28,37 and cardiac MRI. 16 Cross-sectional 3D-TEE annulus measurements have generally been shown to be smaller than MDCT measurements, 11,23,24,38 and a recent study demonstrated that MDCT overestimated whereas 3D-TEE underestimated in vitro phantom annulus diameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown the advantages of 3D assessment of the annulus compared with 2D assessment using multiple modalities, including MDCT, 3,5,6,16,20,35,36 3D-TEE, [7][8][9]11,28,37 and cardiac MRI. 16 Cross-sectional 3D-TEE annulus measurements have generally been shown to be smaller than MDCT measurements, 11,23,24,38 and a recent study demonstrated that MDCT overestimated whereas 3D-TEE underestimated in vitro phantom annulus diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate imaging assessment of the aortic valve annulus is critical for THV sizing. Although the traditional measurement of annular diameter has been performed on the 2-dimensional (2D) echocardiographic long-axis view (sagittal plane), 3 multiple studies have demonstrated the oval shape of the annulus, [4][5][6] with the shortest dimension typically lying in the sagittal plane. Studies across multiple modalities have also shown the advantages of 3-dimensional (3D) assessment of the annulus compared with 2D assessment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Multidimensional computed tomography (MDCT) images are used for the visualization and measurement of aortic root landmarks and distances. 2,3 Despite careful planning, paravalvular leakage 4 and atrioventricular block 5 remain the most frequent complications after TAVI. In this study, a newly developed prototype planning software was used.…”
mentioning
confidence: 99%
“…An oversized prosthesis can result in annular and/or sinotubular junction rupture or coronary artery occlusion, 41,42 whereas under sizing the valve device may result in significant perivalvular leaks and aortic insufficiency, or more catastrophically device migration and embolization. 36,40,42 Definition of the correct annular orientation and axis is complex. Shown in Figure 9 are the similarities and differences between 3-D TEE and CTA using a similar multiplanar reformation technique.…”
mentioning
confidence: 99%